"We ourselves proudly chose death" - Smiljanić, Ivan (Prispevki za novejšo zgodovino, 2024)
The article focuses on the concept of heroic suicide among Yugoslav and especially Slovenian partisans during the Second World War. Partisan command expected fighters to commit suicide in extreme circumstances to avoid ignominious capture, torture and potential treason. After the war, partisan suicides were formally recognized as a heroic act of the highest self-sacrifice, but at the same time they also represented a grey area of Yugoslav memory of the war because they raised challenging moral questions, such as the inadmissibility of suicide from the point of view of Marxist ethics. Opinions expressed in the Yugoslav professional and lay public about the partisan heroic suicides were diverse. Attitudes towards suicide were different in different parts of the country, supposedly depending on the traditional perceptions of death and suicide held by regional or local communities.
Keywords: 2. svetovna vojna; heroic suicide; herojski samomor; Jugoslavija; partisans; partizani; samomori; Second World War; suicide; Yugoslavia; zgodovina